2002
DOI: 10.1002/jsfa.1158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding natural antioxidants on colour stability of paprika

Abstract: We analysed the effect of adding rosemary and tocopherol extracts, two natural antioxidants, on the colour stability of paprika stored at different temperatures and degrees of relative humidity. Any possible synergistic effect of their joint use was also investigated. The experimental data concerning colour loss, as determined by the ASTA 20.1 method, fitted first-and second-order kinetics, which provided the rate constants of colour loss and half-lives of the samples. The first finding concerned the antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…Degradation kinetics of both pigment and color has been found to follow first-order reaction kinetics as have been reported in several other cases (Goncalves et al, 2007;Koca et al, 2007;Ladron de Guevara et al, 2002;Ahmed et al, 2002;Avila and Silva, 1999;Wagner and Warthesen, 1995). The first-order kinetic model is represented as:…”
Section: Calculation Of Kinetic Parametersmentioning
confidence: 95%
“…Degradation kinetics of both pigment and color has been found to follow first-order reaction kinetics as have been reported in several other cases (Goncalves et al, 2007;Koca et al, 2007;Ladron de Guevara et al, 2002;Ahmed et al, 2002;Avila and Silva, 1999;Wagner and Warthesen, 1995). The first-order kinetic model is represented as:…”
Section: Calculation Of Kinetic Parametersmentioning
confidence: 95%
“…The addition of rosmarinic acid resulted in a three times longer time stability. Ladrón de Guevara et al (2002) concluded as well that addition of rosmarinic acid is beneficial to improve the general stability of paprika.…”
Section: Light Stability In the Sun Testmentioning
confidence: 98%
“…Besides, consumers increasingly prefer to avoid synthetic additives in favour of those perceived as natural due to their higher safety and lower toxicity (Balaguer, Gallardo, Infante, Costa-Batllori, & Marzo, 2003;Frost & Sullivan, 2003). Throughout it, the search for antioxidants naturally occurring in plants as alternative to synthetic antioxidants is an interest field to researchers (Bera, Lahiri, & Nag, 2006;Cheah & Abu Hasim, 2000;Ladró n de Guevara et al, 2002). Among them, phenolic extracts from different vegetable products and aromatic plants traditionally used as spices, such as rosemary, are the most used in the food industry (Ibáñ ez et al, 2001;Murphy, Kerry, Buckley, & Gray, 1998).…”
Section: Introductionmentioning
confidence: 99%